Design and evaluation of a ball spline wasp-inspired needle - Bloemberg, Jette; Fung-A-Jou, Zola; Breedveld, Paul; Sakes, Aimée (Frontiers in Bioengineering and Biotechnology, 2024)
In percutaneous interventions, needles are used to reach target locations inside the body. However, when the needle is pushed through the tissue, forces arise at the needle tip and along the needle body, making the needle prone to buckling. Recently, needles that prevent buckling inspired by the ovipositor of female parasitic wasps have been developed. Building on these needle designs, this study proposes a manual actuation unit that allows the operator to drive the wasp-inspired needle through stationary tissue. The needle consists of six 0.3-mm spring steel wires, of which one is advanced while the others are retracted. The advancing needle segment has to overcome a cutting and friction force while the retracting ones experience a friction force in the opposite direction. The actuation unit moves the needle segments in the required sequence using a low-friction ball spline mechanism. The moving components of the needle have low inertia, and its connection to the actuation unit using a ball spline introduces a small friction force, generating a small push force on the needle that facilitates the needle's propulsion into tissue while preventing needle buckling. Experimental testing evaluated the needle's ability to move through stationary 15-wt% gelatin tissue phantoms for different actuation velocities. It was found that the needle moved through the tissue phantoms with mean slip ratios of 0.35, 0.31, and 0.29 for actuation velocities of π, 2π, and 3π rad/s, respectively. Furthermore, evaluation in 15-wt%, 10-wt%, and 5-wt% gelatin tissue phantoms showed that decreasing the gelatin concentration decreased the mean slip ratios from 0.35 to 0.19 and 0.18, respectively. The needle actuation system design is a step forward in developing a waspinspired needle for percutaneous procedures that prevents buckling.